Pengaruh Model Pembelajaran Inkuiri Terbimbing dengan Media Kartu Bergambar Terhadap Kemampuan Berpikir Kritis IPA Siswa Kelas VIII: The Influence of the Guided Inquiry Learning Model with Picture Card Media on the Science Critical Thinking Skills of Eighth-Grade Students - Alawiyah, Nita; A'ini, Zakiyah Fithah; Suryana, Andri (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aimed to determine the influence of the guided inquiry learning model using picture card media on the science critical thinking skills of eighth-grade students on the topic of the respiratory system. The research method employed a quantitative approach with a quasi-experimental design. The research sample consisted of 60 students divided into two groups: class VIII B as the experimental group (30 students) and class VIII C as the control group (30 students) at MTs Darel Azhar Rangkasbitung in 2025. The research instrument was a validated 10-item essay test on science critical thinking skills. Data were analyzed using descriptive statistics, the Liliefors normality test, the F-test for homogeneity, and a t-test for hypothesis testing. The results showed that the average score of the experimental group was 82.06, while the control group's average score was 40.1. The hypothesis test yielded a tcalculated​ value of 19.98, which is greater than the ttable​ value of 2.048 at a 5% significance level. Therefore, it can be concluded that there is a significant influence of the guided inquiry learning model with picture card media on students' science critical thinking skills.